Increasing muscle total carnitine content maintains PDC flux during repeated bouts of very intense exercise - Shannon, C. E.; Ghasemi, R.; Greenhaff, P. L.; Stephens, F. B. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Background: Increasing skeletal muscle total carnitine (TC) content increases pyruvate dehydrogenase complex (PDC) activation and flux during exercise at 80% maximal aerobic capacity (VO2max; [1]). Whether these carnitine-mediated effects on PDC are operative during more intense exercise, when the rate of PDC activation is rapid and flux declines with successive bouts is unknown. We hypothesised that increasing muscle TC content by daily carbohydrate and L-carnitine feeding over 24 wks of exercise training would increase acetyl-group buffering capacity during repeated bouts of exercise at 100% VO2max and thereby maintain PDC flux compared to control. Methods: Ten healthy, untrained male volunteers (Age 23 ± 4 yrs, BMI 24 ± 3kg/m2, VO2max 42 ± 6 ml/kg/min) performed 2 x 3-minute bouts of exercise at 100% VO2max, separated by 5 min of rest, before and after 24 wks of exercise training combined with daily ingestion of 2 x 500ml drinks containing 80g carbohydrate (CHO) or 80g carbohydrate + 2g L-carnitine L-tartrate (1.36g L-carnitine; CARN). Muscle carnitine moieties and PDC activation status (PDCa) was measured in quadriceps muscle biopsy samples taken immediately before and after each bout. Training consisted of 4 bouts of supervised cycling exercise at 100% VO2max, 3/wk. Two-way ANOVA (Bonferonicorrected) was used to compare absolute and delta muscle values; data are expressed as mean ± SE. The University of Nottingham Ethics Committee approved the study. Results: Muscle TC was increased 10% in CARN (20.1 ± 1.8 vs 22.1 ± 2.3; P<0.01) but unchanged in CHO (18.2 ± 1.4 vs 17.2 ± 1.5 mmol/kg dry mass) over 24 wks. There were no differences between CARN and CHO in work output, carnitine acetylation, or PDCa during the first bout of exercise at 24 wks. This resulted in free carnitine availability being 55% greater in CARN vs CHO prior to the second bout of exercise (17.7 ± 2.2 vs 11.3 ± 0.8 mmol/kg dm, respectively; P<0.05). Consequently, carnitine acetylation during the second bout was greater in CARN vs CHO (3.8 ± 2.4 vs 0.1 ± 1.4 mmol/kg dm; P<0.05), despite similar work output (43.6 ± 6.0 vs 44.5 ± 3.9 kJ) and increases in PDCa (5.9 ± 3.0 vs 3.9 ± 3.7 nmol/min/mg protein, respectively). Conclusions: Daily carbohydrate and L-carnitine feeding increased muscle TC content over 24 wks of exercise training. This resulted in PDC flux being maintained during a second bout of very intense exercise compared to control, despite similar PDC activation. Increasing muscle free carnitine content therefore improves muscle acetyl group buffering capacity during repeated bouts of very intense exercise, resulting in enhanced PDC flux.